2024
DOI: 10.1021/acs.est.4c00740
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Land Use Change on Molecular Composition and Concentration of Organic Matter in an Oxisol

Zongtang Yang,
Tsutomu Ohno,
Balwant Singh

Abstract: Land use change from native vegetation to cropping can significantly affect the quantity and quality of soil organic matter (SOM). However, it remains unclear how the chemical composition of SOM is affected by such changes. This study employed a sequential chemical extraction to partition SOM from an Oxisol into several distinct fractions: water-soluble fractions (ultrapure water (W)), organometal complexes (sodium pyrophosphate (PP)), short-range ordered (SRO) oxides (hydroxylamine-HCl (HH)), and well-crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 92 publications
(251 reference statements)
0
2
0
Order By: Relevance
“…Yang et al recently published an article in Environmental Science & Technology titled “Effect of Land Use Change on Molecular Composition and Concentration of Organic Matter in an Oxisol” . In this study, Yang et al employed a sequential chemical extraction to separate soil organic matter (SOM) from an Oxisol into several distinct fractions: water-soluble fractions [ultrapure water (W)], organometal complexes [sodium pyrophosphate (PP)], short-range ordered (SRO) oxides [hydroxylamine-HCl (HH)], and well-crystalline oxides [dithionite-HCl (DH)].…”
mentioning
confidence: 99%
“…Yang et al recently published an article in Environmental Science & Technology titled “Effect of Land Use Change on Molecular Composition and Concentration of Organic Matter in an Oxisol” . In this study, Yang et al employed a sequential chemical extraction to separate soil organic matter (SOM) from an Oxisol into several distinct fractions: water-soluble fractions [ultrapure water (W)], organometal complexes [sodium pyrophosphate (PP)], short-range ordered (SRO) oxides [hydroxylamine-HCl (HH)], and well-crystalline oxides [dithionite-HCl (DH)].…”
mentioning
confidence: 99%
“…We value the comments made by Lv and Cao on our recently published article on the effect of land use change on the molecular composition of organic matter (OM) and soil organic carbon (SOC) concentration for an Oxisol. We reported that land use change from native vegetation to cropping resulted in a decrease in OC concentration and had minor effects on the molecular composition of OM.…”
mentioning
confidence: 99%